Availability and use of neighborhood resources by older people with osteoarthritis: Results from the European Project on OSteoArthritis. (January 2016) - van der Pas, S.; Schaap, L.A.; Castell, M.V.; Cooper, C.; Denkinger, M.; Edwards, M.H.; Herbolsheimer, F.; Maggi, S.; Sánchez-Martinez, M.; Pedersen, N.L.; Peter, R.; Zambon, S.; et al.
Abstract: This study examines the availability and use of neighborhood resources in relation to clinical lower limb osteoarthritis (LLOA) in older participants from six European countries. Of the 2757 participants (65–85 years), 22.7% had LLOA. Participants with LLOA made more use of places to sit (OR=2.50; CI: 1.36–4.60 in the UK), and less use of parks and walking areas (OR=0.30; CI: 0.12–0.75 in Sweden), compared to participants without LLOA, particularly in countries with high availability of resources. The results suggest that specific features of the environment impact the use of neighborhood resources by older adults with LLOA. Highlights: LLOA is associated with more use of places to sit and rest, and with less use of parks. Availability of neighborhood resources varies between the six European countries. Physical environment features impact the use of the environment by older adults with OA in Europe.